Local Spin-State Tuning of Iron Single-Atom Electrocatalyst by S-Coordinated Doping for Kinetics-Boosted Ammonia Synthesis - Li, Yan (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.